POSTURAL STABILITY EXERCISE LEBIH MENINGKATKAN FLEKSIBILITAS LUMBAL DIBANDINGKAN STATIC STRETCHING EXERCISE PADA PENJAHIT DI KOTA DENPASAR - Gita Karunia Saraswati, Ni Luh Putu; Sutjana, I Dewa Putu; -, Wahyuddin; Tianing, Ni Wayan; Sri Handari Adiputra, Luh Made Indah; Irfan, Muh. (Sport and Fitness Journal; Volume 7, No.1, Januari 2019, 2019)
ABSTRACT Background: Tailor work characteristics such as sitting static and bending can trigger complaints such as lower back area muscle tension which if left untreated can cause a decrease in lumbar flexibility. Purpose: to prove postural stability exercise is more to increase lumbar flexibility than static stretching exercise on tailors in Denpasar City. Method: This study was an experimental study with pre and post test control group design. The study sample consisted of 30 people divided into two groups. Group 1 given static stretching exercise, while Group 2 given postural stability exercise. Measurement of lumbar flexibility using a modified-modified Schoober test. Result: Paired Sample t-test in Group 1 and Group 2 showed p value p <0.05 which showed that there were significant changes after giving training to each group. Furthermore, a comparison test between Group 1 and Group 2 used independent sample t-test and obtained p <0.05. This result showed that there are significant differences between the two groups. Conclusion: postural stability exercise increases lumbar flexibility more than static stretching exercise for tailors in Denpasar City. Keywords: lumbar flexibility, static stretching exercise, postural stability exercise, tailor.